Direct growth of MoS2 single crystals on polyimide substrates. (12th May 2017) - Gong, Yongji; Li, Bo; Ye, Gonglan; Yang, Shize; Zou, Xiaolong; Lei, Sidong; Jin, Zehua; Bianco, Elisabeth; Vinod, Soumya; Yakobson, Boris I; Lou, Jun; Vajtai, Robert; et al.
Abstract: Two dimensional (2D) materials are optimum building blocks for flexible electronics due to their outstanding electrical and mechanical properties and ultimately atomically-thin structures. Unfortunately, to date, flexible electronics based on high quality 2D monolayers can only be obtained by various transfer technologies—processes that risk contamination and damage of 2D crystals. Here, we report a simple chemical vapor deposition (CVD) method to directly grow monolayer MoS2 single crystals on polyimide (PI) substrates using ammonium molybdate as a precursor. Growth is performed at 450 °C, at which temperature PI is still insulating and flexible. A Flexible photodetector was built directly on the MoS2 /PI and showed strong photoresponse. This is the first successful application of a scalable synthesis method (CVD) on a polymeric substrate. Our research represents an important step toward scalable fabrication of 2D flexible electronics.